Integration Of Local Wisdom In Environmental Management: Environmental Ethics Perspective And Harmonization Of National Law - Ismelina Farma Rahayu; Tariparlaut Tariparlaut; Aswin Aswin; Dian Agustian Perdana; Reza Wahyu Pratama (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Environmental damage that occurs in various countries today requires a new approach to environmental management, where conventional methods that rely on technology and modern laws have not been able to overcome the complexity of contemporary environmental problems. Indonesia as a country with cultural diversity has a wealth of traditional knowledge that has proven effective in preserving nature for centuries. This research aims to analyze how to integrate local wisdom into the national environmental management system through the perspective of environmental ethics and find a model for harmonizing national law with local values ​​without eliminating legal certainty. The research method uses a normative juridical approach with statutory, conceptual, and philosophical analysis through literature study of primary, secondary, and tertiary legal materials with descriptive qualitative analysis and deductive reasoning. The results show that Indonesian local wisdom has advantages in applying the principles of sustainable environmental ethics through an ecocentric approach that recognizes the intrinsic value of nature, in contrast to modern approaches that tend to be anthropocentric. Harmonization between national law and customary law systems requires a legal pluralism approach that recognizes the coexistence of both systems to create synergies in environmental management. The implementation model of local wisdom integration must be adapted to the specific characteristics of each region through a bottom-up participatory methodology that places local communities as active subjects in the planning, implementation and evaluation of environmental policies to realize sustainable environmental management based on local cultural values.